Three-Dimensional Finite Element Simulations for the Thermal Characteristics of PCRAMs with Different Buffer Layer Materials - 龚岳峰 宋志棠 凌云 刘燕 李宜瑾 封松林 (Chinese physics letters, 2010)
Simulation of the heat consumption in phase change random access memories （PCRAMs） is investigated by a three-dimensional finite element model. It is revealed that the thermal conductivity and electrical conductivity of the buffer layer are crucial in controlling the heating efficiency in RESET process. The buffer layer mater/Ms W, TiN, WOa, Ti02 and poly-germanium （poly-Ge） are applied in the simulation respectively, and compared with each other. The simulation results show that limitation of electrical conductivity is effective on heating efficiency and the limitation of thermal conductivity is important on the reliable RESET process.